Boosting Carrier Mobility of Synthetic Few Layer Graphene on SiO2 by Interlayer Rotation and Decoupling. Issue 14 (22nd May 2018) - Wu, Xiangyu; Chuang, Yaoteng; Contino, Antonino; Sorée, Bart; Brems, Steven; Tokei, Zsolt; Heyns, Marc; Huyghebaert, Cedric; Asselberghs, Inge
Abstract: The role of interlayer rotation on the electrical transport of few layer graphene (FLG) is rarely considered. In this paper, the impact of twisting angle on physical and electrical properties of synthetic single crystal bilayer and few layer graphene deposited on thermal SiO2 substrate is systematically studied. Bernal AB‐stacked graphene layers show low carrier mobility due to strong interlayer coupling and substrate scattering. A dramatic increase in carrier mobility and conductivity is observed when the graphene layers are twisted. A field effect mobility up to 15000 cm 2 V −1 s −1 and 460 nm mean free path is measured on a twisted three‐layer graphene at room temperature is among the highest for graphene transferred to SiO2 . In average, twisted graphene shows a fivefold improvement compared to AB stacked graphene in terms of mobility and conductivity, regardless of twist angles. Abstract : The electrical properties of twisted graphene layers grown on Pt foil and subsequently transferred to SiO2 are investigated. The twisting layers can be identified by Raman and optical inspection. Twisted graphene layers exhibit much higher carrier mobility and conductivity than single layer and AB‐stacked layers, regardless of the exact twist angles.